Analysis of the proficiency of fully-connected neural networks in the process of classifying digital images : benchmark of different classification algorithms on high-level image features from convolutional layers - Janke, Jonathan Gabriel Martin (2019)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics